2008
DOI: 10.1038/pcan.2008.40
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nerve sparing on surgical margins and biochemical recurrence: results from the SEARCH database

Abstract: The effects of nerve sparing on the risk of positive surgical margins (PSMs) and biochemical recurrence after radical prostatectomy (RP) remain controversial. We examined data from 1018 men treated by RP between 1988 and 2006 at five centers in the Shared Equal Access Regional Cancer Hospital database. Neither bilateral nor unilateral nerve-sparing techniques were associated with a higher risk of PSM; on multivariate analysis of individual sides, the risk of PSM on either side was not increased by nerve sparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Table 1 lists the characteristics of the study population for all the study subjects, as well as a subset analysis of men who had a biopsy Gleason sum ≤6. During the follow-up period, 46 (44.7%) of all study subjects had a PSA recurrence, which is in the range with previous reports4.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Table 1 lists the characteristics of the study population for all the study subjects, as well as a subset analysis of men who had a biopsy Gleason sum ≤6. During the follow-up period, 46 (44.7%) of all study subjects had a PSA recurrence, which is in the range with previous reports4.…”
Section: Resultssupporting
confidence: 84%
“…Pathological stage, the most reliable predictor of tumor progression, recurrence and overall disease outcome, is only available if a patient chooses to undergo radical prostatectomy. Several limiting factors surrounding the use of staging and common clinical tumor markers argue for the development of more reliable prognostic markers prior to therapeutic intervention24. To meet this need, efforts have focused on development of molecular markers available at the time of biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that preoperative clinicopathological features predict margin status more accurately than NSS technique. Several other single‐institutional [10–12,17] and multi‐institutional [13] studies have also reported that NSS technique is not a risk factor for PSMs. Nelles et al .…”
Section: Discussionmentioning
confidence: 89%
“…Several single‐surgeon [11,12] and multicenter [13] studies have found no significant association between NSS and PSM after adjusting for other risk factors such as age, PSA level, Gleason grade, P stage and year of surgery. Billis et al .…”
Section: Introductionmentioning
confidence: 99%
“…Two large database studies of RPs did not report a correlation between the 2 factors [7,21]. In contrast, in a large series of patients having undergone ORP, an increase in the PSM from 7.8 to 13.9% was seen when performing a nerve-sparing prostatectomy, irrespective of tumour stage [22].…”
Section: Discussionmentioning
confidence: 99%